Domain-specific cognitive impairment 6 months after stroke: The value of early cognitive screening - Milosevich, ET; Moore, MJ; Pendlebury, ST; Demeyere, N (SAGE Publications, 2023)
Background:: Cognitive screening following stroke is widely recommended, yet few studies have considered the prognostic value of acute domain-specific function for longer-term cognitive outcome. Identifying which post-stroke cognitive impairments more commonly occur, recover, and persist, and which impairments hold prognostic value, could inform care planning, and resource allocation. Aims:: This study aimed to determine the prevalence of domain-specific impairment acutely and at 6 months, assess the proportion of change in cognitive performance, and examine the prognostic value of acute domain-specific cognitive screening. Methods:: A prospective stroke cohort completed the Oxford Cognitive Screen acutely (⩽2 weeks) and 6 months post-stroke. We determined the prevalence of acute and 6-month domain-specific impairment and proportion of change in performance from acute to 6 months. Hierarchical multivariable regression was used to predict global and domain-specific cognitive impairment at 6 months adjusted for demographic/vascular factors, stroke severity, and lesion volume. Results:: A total of 430 stroke survivors (mean/SD age 73.9/12.5 years, 46.5% female, median/interquartile range (IQR) National Institute of Health Stroke Scale (NIHSS) 5/2–10) completed 6-month follow-up. Acutely, domain-specific impairments were highly prevalent ranging from 26.7% (n = 112) in praxis to 46.8% (n = 183) in attention. At 6 months, the proportion of domain-specific recovery was highest in praxis (n = 73, 71%) and lowest in language (n = 89, 46%) and memory (n = 82, 48%). Severity of 6-month cognitive impairment was best predicted by the addition of acute cognitive impairment (adj R2 = 0.298, p < 0.0001) over demographic and clinical factors alone (adj R2 = 0.105, p < 0.0001). Acute cognitive function was the strongest predictor of 6-month cognitive performance (p < 0.0001). Acute domain-specific impairments in memory (p < 0.0001), language (p < 0.0001), and praxis (p < 0.0001) significantly predicted overall severity of cognitive impairment at 6 months. Conclusion:: Post-stroke cognitive impairment is highly prevalent across all domains acutely, while impairments in language, memory, and attention predominate at 6 months. Early domain-specific screening can provide valuable prognostic information for longer-term cognitive outcomes.